2023
DOI: 10.1029/2022av000837
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Wave‐Induced Attenuation in Saturated Metapelite and the Band‐Limitation of Low‐Frequency Earthquakes

Abstract: The elastic waves produced by "typical" small magnitude earthquakes (M ω between 1 and 3) have a recorded frequency range between 1 and 30 Hz (Shelly et al., 2007). In contrast, the families of earthquakes known as very low-frequency earthquakes (VLFEs) (Ide et al., 2007;Obara & Kato, 2016) and low-frequency earthquakes (LFEs) (Obara, 2002;Rogers & Dragert, 2003;Schwartz & Rokosky, 2007) are depleted in high frequencies when compared to small "typical" earthquakes of similar magnitudes (Figure 1a). The frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
3
1
Order By: Relevance
“…Assuming that rays from deep earthquakes pass through the region where low-frequency events occur in the orange column, the observed difference in spectra between regular earthquakes and low-frequency earthquakes cannot be explained by the greatest possible attenuation below the subduction interface where low-frequency earthquakes occur, as estimated from intraslab earthquakes. This contrasts with recent experimental work on lithologies suspected to host low-frequency earthquakes (36). Our results indicate that the absence of high-frequency components in low-frequency seismic events is not primarily controlled by abnormally high attenuation.…”
Section: Earthquake-like Spectral Shape Of Low-frequency Earthquakescontrasting
confidence: 99%
See 1 more Smart Citation
“…Assuming that rays from deep earthquakes pass through the region where low-frequency events occur in the orange column, the observed difference in spectra between regular earthquakes and low-frequency earthquakes cannot be explained by the greatest possible attenuation below the subduction interface where low-frequency earthquakes occur, as estimated from intraslab earthquakes. This contrasts with recent experimental work on lithologies suspected to host low-frequency earthquakes (36). Our results indicate that the absence of high-frequency components in low-frequency seismic events is not primarily controlled by abnormally high attenuation.…”
Section: Earthquake-like Spectral Shape Of Low-frequency Earthquakescontrasting
confidence: 99%
“…The presence of fluids, supported here by our local estimates of 1D seismic velocity and attenuation, can not only affect the dynamic rupture propagation by reducing dynamic friction ( 37 ) but also slow down rupture speeds through dilatancy strengthening ( 38 ). Compared to dry conditions, fluids can cause frequency-dependent attenuation to dominate under saturated conditions ( 36 ) that is difficult to model. We sidestep this challenge by correcting low-frequency earthquake spectra with empirical estimates of attenuation that do not rely on a given model ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the proposed models are frequency-independent and do not distinguish between scattering and intrinsic attenuation. Laboratory measurements on samples of the Orocopia schist which constitutes part of the crust in Southern California show increases in intrinsic attenuation as pore pressure increases 41 confirming that measurable changes in seismic attenuation can reflect changes in rock-fluid properties. Here, instead of using the regional seismic network only, we take advantage of the densely distributed seismic nodes of the temporary BASIN network (Fig.…”
Section: Introductionmentioning
confidence: 82%
“…While the band‐limited nature of LFEs due to high‐frequency depletion has been assumed to represent slower fault rupture and slip, it can also occur due to near‐source attenuation associated with high fluid pressure in the LVZ (Bostock et al., 2017; Gomberg et al., 2012). Recently, laboratory experiments have demonstrated that water‐saturated metapelite at low effective pressure can cause high‐frequency attenuation (Fliedner & French, 2023). Shear and tensile failures in quartz veins produce high‐frequency components, but may be attenuated in metapelite and metabasite, which form a high fluid pressure zone tens to hundreds of meters thick.…”
Section: Discussionmentioning
confidence: 99%